Effect of Two Different Injection Techniques of Local Anaesthetic in Ultrasound Guided Supraclavicular Brachial Plexus Block on Diaphragmatic Motility - Prasad, Jagat Narayan; Ghimire, Ashish; Chaudhary, Pashupati; Guddy, KM; Sarraf, Deependra Prasad (Journal of BP Koirala Institute of Health Sciences, 2024)
Background: Deposition of local anesthetic (LA) caudal and posterolateral to brachial plexus might result in less hemidaiphragmatic paralysis. Objective was to compare the effect of two different injection techniques of 0.5% Ropivacaine in ultrasound guided supraclavicular brachial plexus block (BPB) on diaphragmatic motility. Methods: A prospective randomized double-blinded comparative study was conducted among adults undergoing right upper limb surgery. In group A (n = 17), 20 mL 0.5% ropivacaine was injected caudal and posterolateral to the brachial plexus. In group B (n = 17), two aliquots each of 10 mL ropivacaine were injected at two separate locations within the plexus sheath. Diaphragmatic excursion and success of blockade were measured at 15 and 30 minutes. Results: All patients in group B had sensory and motor blockade in both median and musculocutaneous nerve territories at 15 minutes while it was only in 10 patients (58.82%) in median nerve territory and 7 patients (41.18%) in musculocutaneous nerve territory in group A (P-value< 0.05). At 30 minutes, 17 (100%) patients in group B and 16 (94.12%) patients in group A had successful blockade (p-value>0.05). At 15 minutes, complete hemidiaphragmatic paralysis was seen in 10 (58.82%) patients in group B and three (17.65%) patients in group A (p-value<0.05). At 30 minutes, it was seen in 11 (64.71%) patients in group B and three (17.65%) patients in group A (p-value<0.05). Conclusion: LA at two sites resulted in more hemidiaphragmatic paralysis with similar block success rate as compared to LA injection at a single site.